Design of the analog-to-digital converter using threshold inverter quantization approach - Bui, Anh Khoa (2012)
This project is to design Flash Analog-to-digital Converter (ADC) using Threshold Inverter Quantization (TIQ) method. The TIQ-based Flash ADC must be designed to satisfy the issues of low-power and low-voltage implementations. TIQ is a creative method that is introduced by Ali Tangel. It makes use of 2-cascaded inverters to replace the conventional comparator. The TIQ comparator uses it inverter’s threshold voltage as the internal voltage reference.